Downstream Passage of Fish Larvae at the Salto Grande Dam on the Uruguay River. (6th April 2016) - Fuentes, C. M.; Gómez, M. I.; Brown, D. R.; Arcelus, A.; Espinach Ros, A.
Abstract: We evaluated the passage of early‐stage fishes through the Salto Grande Dam using high‐frequency downstream ichthyoplankton monitoring and five surveys involving samples taken upstream and downstream of the dam. Eggs and larvae of migratory fishes were captured downstream of the dam, usually during high discharges. Upstream and downstream larvae were frequently unyolked, which corresponds to individuals aged 4+ days, and represents a time significantly longer than that required for the displacement of the water mass from the dam to the sampling location. In low flow rate surveys, fish larvae of the same species and degree of development were captured immediately upstream and at 1, 10, 24 and 40 km downstream of the dam. The densities and percentage of Pimelodinae larvae captured alive by short time and low speed tows were similar upstream and downstream of the dam, indicating that larval mortality was a result of sampling and not to the passage through the turbines. The results show that the larvae of fish that spawn in the middle section are partly transported to the lower section, and suggest that both spillway and turbine discharge should be considered part of the passage. We also found evidence that the passage of small and fragile Pimelodinae larvae through the Salto Grande Kaplan turbines does not significantly affect survival rates. Copyright © 2016 John Wiley & Sons, Ltd.